HIDROPONIK SEBAGAI BENTUK PEMANFAATAN LAHAN SEMPIT UNTUK PENINGKATAN PENDAPATAN RUMAH TANGGA DI NAGARI SUNGAI KAMUYANG - Devi Yulia Rahmi; Ranny Fitriana Faisal; Agestayani Agestayani; Susiana Susiana; Winny Alna Marlina; Fatma Poni Mardiah; Erizal Erizal; Faisal Ali Ahmad; Musbatiq Srivani (LPPM Universitas Andalas, 2020)
Narrow land is a problem for conventional agriculture to grow crops Management of small area can be overcome with a hydroponic system that utilizes technology in farming. Small area owned by households can be maximized for agriculture. However, household stigma is still fixed on conventional agriculture by managing large tracts of land. This stigma must then be changed by giving literacy to households about farming using the hydroponic method. Based on this understanding, Department of Management Campus II Universitas Andalas held socialization and training with the theme